TECHNICAL ANALYSIS FOR BUY OR SELL DECISIONS IN CRYPTOCURRENCY (BITCOIN): University Pembangunan Nasional Veteran East Java, Surabaya - Yumna, Hartsa Fayi; Taufiq, Muhammad; Utami, Anisa Fitria (PT. Media Edutama Nusantara, 2024)
The purpose of this study is to determine how to provide recommendations for buy or sell decisions based on the price movements of cryptocurrency using technical analysis. This study employs a qualitative approach because the goal is to deeply and thoroughly understand the technical patterns in Bitcoin price charts to make informed buy and sell decisions. In this research, the data analysis technique used is Content Analysis. Content analysis is a research method that allows for the subjective interpretation of various types of data through a systematic classification process and the identification of themes or patterns. In conclusion, the technical patterns identified during the period from June 2022 to October 2023 provide strong signals for buy decisions. The combination of volume confirmation, price movements above the 200-day moving average, chart patterns, breakouts, major trend patterns, and the integration of supporting theories provides a solid foundation for this analysis and reinforces the confidence that prices are likely to rise.